2010
DOI: 10.1007/s12572-011-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity based microstructure and strength prediction of plain and modified concretes

Abstract: Electrical response of cementitious systems can be used to understand the evolving microstructure, and thus to provide indications of the mechanical and durability performance of such systems. This paper deals with the use of a generalized effective medium (GEM) theory to predict the porosity of cement pastes and concretes containing several cement replacement materials. Methodologies to obtain the pore solution conductivities and an equivalent soild phase conductivity in the case of concretes are outlined. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Garboczi and Bentz [ 65 ] indicated that the resistivity of C-S-H was about 400 times as much as that of pore solution (M = 400). While other researchers reported relatively low values of 100 [ 63 ] and 133.3 [ 67 ].…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…Garboczi and Bentz [ 65 ] indicated that the resistivity of C-S-H was about 400 times as much as that of pore solution (M = 400). While other researchers reported relatively low values of 100 [ 63 ] and 133.3 [ 67 ].…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…11a,b that even under the same curing condition, the ACISs are significantly different with different conductive media, the diameters of the impedance spectrum arcs are: CG > SS > SCH. According to the generalized effective medium (GEM) theory 50,51 , generally electrical conduction is more likely (12) 5Z t4 (p = 10) − Z t4 (p = 2) = 4Z 4ic (13) Z 4ic = 5Z t4 (p = 10) − Z t4 (p = 2) 4 www.nature.com/scientificreports/ to take place through the more conductible phases for a composite material with different electrical conductivity for each component 52 . For a cement paste specimen, the conductivity of solid phases (cement clinkers, hydration products) and vapor phases are lower several orders than the liquid phase 53,54 , therefore, the impedance of the specimen is mainly determined by the pore structure and pore solution.…”
Section: Evaluation Of the Contact Impedance In The Two-point Measurementioning
confidence: 99%
“…The specification of the service-life/performance/durability of reinforced concrete by means a single parameter is the holy grail of the engineer and hence a subject of intense research interest (see, for example, Neithalath, Persun, and Manchiryal, 2010;Muigai, Moyo and Alexander, 2012;Spragg et al, 2013;Andrade, d'Andrea and Rebolledo, 2014;Nganga, Alexander and Beushausen, 2015;Merioua, Bezzar and Ghomari, 2015). The challenges posed by a performance-based testing and specification approach to improve service life of concrete structures have been acknowledged (Beushausen and Fernandez-Luco, 2015).…”
Section: Performance Testingmentioning
confidence: 99%